The Development of Spatial Representation Through Teaching Block-Building in Kindergartners - Cai, Liman; Luo, Jiutong; Zhang, Hui; Ying, Jinling (Frontiers in Psychology, 2020)
This study investigated the effects of the teaching block-building intervention on overall spatial representation and its three sub-forms, namely linguistic, graphic and model representations, in kindergartners. Eighty-four children (39 girls and 45 boys), aged 5–6 years old, were randomly selected and equally divided into two groups, i.e., experimental group and control group. The experimental group received the intervention of teaching block-building for 14 weeks (45 min each time, once a week), while children in the control group freely played with blocks for the equivalent time. Children’s spatial representation performances were measured in both pre- and post-tests by the Experimental Tasks of Spatial Representation for Children. The results showed that: (1) teaching block-building could promote not only the overall spatial representation but also all three sub-forms of spatial representations; (2) there was no gender differences regarding the effect of teaching block-building on neither the overall nor three sub-forms of spatial representations; (3) after the intervention, the diversity of children’s choices regarding the use of sub-forms spatial representations was also promoted in the experimental group. In summary, these results contributed to a comprehensive and systematic understanding of the effects of teaching block-building on spatial representation among children in kindergartens.